2020
DOI: 10.1021/acs.jcim.0c00945
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Flavin-Mediated Oxidation: Hydride or Hydrogen-Atom Transfer?

Abstract: Flavins are versatile biological cofactors which catalyze proton-coupled electron transfers (PCET) with varying number and coupling of electrons. Flavin mediated oxidation of nicotinamide adenine dinucleotide (NADH) and of succinate, initial redox reactions in cellular respiration, were examined here with multiconfigurational quantum chemical calculations and a simple analysis of the wave-function proposed to quantify electron transfer along the proton reaction coordinate. The mechanism of NADH oxidation is a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…They found that the oxidation of 1-methylnicotinamide by lumiflavin proceeded by hydride transfer. 30 As depicted by the spin density surface of Fig. 2b (and the Mulliken spin density values of Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…They found that the oxidation of 1-methylnicotinamide by lumiflavin proceeded by hydride transfer. 30 As depicted by the spin density surface of Fig. 2b (and the Mulliken spin density values of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Similar initial guess structures were also obtained by others in studies concerning flavins and nicotinamide derivatives. 29,30 Conversely, Vianello et al 31 found that hydride transfer from amino donors to the flavin cofactor of the Monoamine oxidase (MAO) flavoenzyme did not involve p-p stacked adducts, rather more angular structures.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the pitfalls of using population analysis to examine reaction mechanisms recently discussed in the context of PCET 20,76 are partially mitigated when summing populations over whole chemical groups, 77 such as in Q or imidazole groups used here. Table 2 shows population analysis for reactant and product geometries of proton transfer.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Several enzymes employ PCET as a strategy to decrease the overpotential that would have to be surmounted for electron or proton transfer alone. , Their catalytic mechanisms have been studied with molecular simulation, particularly for analysis of the tunneling behavior and participation of electronic excited states. Although various aspects of cytochrome bc 1 have already been investigated by simulations, proton tunneling and nonadiabatic effects of reactions in the Q o site have received less attention. , …”
Section: Introductionmentioning
confidence: 99%
“…[2,3] F I G U R E 1 Structure and heavy-atom numbering for the isoalloxazine ring, the core group of flavins responsible for their redox and photophysical properties Redox flavoproteins participate in single-electron transfer reactions, [4] in oxygen-dependent oxidation, [5] and in proton-coupled electron transfers (PCET) with varying number of electrons. [2,6,7] Flavin chromophores are found in blue-light protein receptors [3] and in photodependent enzymes. [8] Recently, the biological role of flavins as general acid-base catalysts has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%